Abdominal massage to reduce constipation in the intensive care unit - Dudella Desnani Firman Yasin; Eny Erlinda Widyaastuti; Christine Handayani Siburian; Arif Rahman Aceh (Nursing and Health Sciences Journal (NHSJ), 2025)
Mechanical ventilation is a positive and negative pressure breathing aid that maintains and improves oxygen ventilation in long-term positions. One of the impacts of the ventilation Mechanism is constipation. Constipation can hinder the weaning process; management of non-pharmacological constipation is by performing abdominal massage intervention. This study aims to describe the use of abdominal massage in the treatment of constipation in patients undergoing mechanical ventilation in the ICU. Case studies were used in this study, using the approach of nurses who provide care. The Results show that in client 1, where no abdominal distension was found (score 5), no mass was felt on the rectal (score 5), peristaltic increased from Which No heard became 19 x/ minute (score 5), and the Chapter on day 3 (score 4) with soft and solid stool consistency (score 5). Client 2 with results showing no distension of the abdomen (score 5), no palpable mass in the rectum (score 5), intestinal peristalsis increased from 5x/minute to 23x/ minute (score 5), and defecation on the day to 3 (score 4) with consistency of feces soft and solid (score 5). The application of massage to the abdomen improves fecal elimination in constipated patients with mechanical ventilation installed in the ICU. Healthcare institutions should foster a culture that supports the integration of complementary therapies into standard nursing practices. This could involve developing guidelines and protocols for the use of massage therapy in various clinical settings, thereby standardizing care practices and ensuring that all patients receive the benefits of such interventions.